A Colorimetric Method for the Determination of Oil Deposit on Citrus Leaves. Issue 6 (27th August 2014) - McCall, G. L.; Kagy, J. F.
Abstract : The determination of the quantity of petroleum oil deposited on the leaves of a citrus tree by various spray emulsions has been the subject of considerable discussion and research. It is of primary importance to know the amount of oil deposited, in order to correlate the data with the factors of insect toxicity and injury to the tree. When oil sprays are tested to ascertain their respective toxicity to insects, it is very easy to draw erroneous conclusions with regard to differences in effectiveness. In reality, the apparent differences may be due to the fact that under a given set of conditions one spray emulsion will deposit a larger amount of oil than will another. A slight change in the physical or chemical properties of the emulsion may affect the results very markedly (Hensill & Hoskins 1935, Ben-Amotz & Hoskins 1937, Brown & Hoskins 1939). The accurate determination of the oil deposited is therefore of the greatest importance.